An Experimental Study for Municipal Organic Waste and Sludge Treated by Hydrothermal Carbonization - Vega-Viveros, R; Cubillos-Montecino, F; Diaz-Robles, L; Espinoza-Perez, A; Vallejo-Gallardo, F (Italian Association of Chemical Engineering - AIDIC, 2020)
The use of firewood and other biomass-based fuels have generated severe environmental pollution problems due high particulate matter emissions. Additionally, developing countries face considerable challenges in aspects related to the final disposal of organic waste in sanitary landfills that are already overflowed, and that constitutes a serious problem. In the last years, the search for alternative energy sources based on organic waste valorization has gained popularity. For waste biomass conversion, Hydrothermal Carbonization (HTC) has some advantages: Low process temperatures required and the ability to work with biomass of different compositions and high moisture. Two groups of urban waste were considered in this investigation: 1) organic fraction of municipal solid waste (OFMSW) and 2) digested sludge (DS) from a water treatment plant. An Experimental Design was developed to study the effect of the blend composition with different OFMSW:DS ratios, reaction time (0.5 and 1 h) and temperature (190 and 220°C) on the Mass Yield (MY), the Higher Heating Value (HHV), Energy Densification Ratio (EDR) and Energy Yield (EY). The response equations had an average determination coefficient (R2) of 0.95 with an RMSE of 5.9 %. The results showed that temperature was the most significant variable on the MY (-9.8 %) and the HHV (+8.7 %). Blend 2, with a greater amount of pruning waste, had higher MY and HHV. Blend 1 had the highest percentage of food waste and sludge, and, therefore, the highest MY values. The energy yield determined for the three mixtures was about 80 %, indicating that HTC is a feasible technology for the recovery of municipal waste biomass and sludge. © 2020, AIDIC Servizi S.r.l.